Knowledge management and higher education a critical analysis - Metcalfe, Amy 1967-.; Gale Group (Hershey, Penn. Information Science Pub., 2006)
Using various social science perspectives, this book provides critical analyses of knowledge management in higher education, with an emphasis on unintended consequences and future implications.
The application of knowledge management in higher education -- Administrative issues and knowledge management -- Knowledge management of teaching and learning -- Case studies -- Resources.
Electronic reproduction.
Keywords: Education, Higher -- Economic aspects; Knowledge management; Education, Higher -- Effect of technological innovations on; Electronic books